PERLINDUNGAN HUKUM TERHADAP HAK PENDIDIKAN SISWI HAMIL LUAR NIKAH MENURUT HUKUM POSITIF DAN HUKUM ISLAM - Zahirah, Fairuz; Mufidah; Rahim, Abdur (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Legal protection means providing shelter to human rights that have been harmed by others, and this protection is provided by law enforcement officers to the community to ensure a sense of security. A schoolgirl who becomes pregnant out of wedlock, as part of the community, may feel her right to education revoked, where she should be the one who most deserves legal protection from the state. The right to education is enshrined in national law. Meanwhile, Islam also obliges its followers to seek knowledge. The purpose of this research is to understand legal protection of the right to education for pregnant schoolgirls out of wedlock, according to both positive law and Islamic law. The research conducted is library research based on the study and analysis of texts, employing a statute approach and a conceptual approach. The data sources used are literature data, with document analysis relevant to the research. The data obtained is then processed and analyzed in depth to gain insights or conclusions relevant to the issues being studied. The conclusion derived from this study is that the legal protection of the right to education for pregnant schoolgirls out of wedlock is written in the 1945 Constitution Article 31, which means education is a right that must be received by Indonesian citizens. The protection of pregnant schoolgirls to ensure they still receive their educational rights needs to be a focus of the government, so that no generation is left behind in education. In Islamic law, education is also very important, in accordance with the concept of maqasid shariah, particularly the principle of protecting the intellect (Hifdz al-Aql), the principle of protecting life (Hifdz al-Nafs), which can be a basis for protecting the life of a pregnant schoolgirl, and the principle of protecting offspring (Hifdz al-Nasl) to safeguard the unborn child. Keywords: Legal Protection, Right to Education, Pregnant Out of Wedlock, Positive Law, Islamic Law